ON CLASSES OF ANALYTIC FUNCTIONS CONTAINING GENERALIZATION OF INTEGRAL OPERATOR - Darus, Maslina; Ibrahim, Rabha W. (Journal of the Indonesian Mathematical Society, 2011)
New classes containing generalization of integral operator are introduced. Characterization and other properties of these classes are investigated. Further, Fekete-Szego functional for these classes are also given.DOI :Â http://dx.doi.org/10.22342/jims.17.1.11.29-38